2002
DOI: 10.1097/00004872-200201000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Intraluminal pressure modulates eicosanoid enzyme expression in vascular endothelium of intact human conduit vessels at physiological levels of shear stress

Abstract: Intraluminal pressure has differential effects on gene and protein expression of key eicosanoid enzymes and biosynthesis of prostanoid metabolites in intact human conduit vessels. The new, computerized biomechanical perfusion system may be a useful tool to elucidate specific effects of various biomechanical forces on intact mammalian conduit vessels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Alternatively, because testosterone exposure occurred in vivo, we cannot rule out indirect effects that could modulate the levels of TxA 2 synthase. For example, changes in shear stress were recently shown in human umbilical veins to affect TxA 2 expression; however, unlike testosterone exposure, prostacyclin synthase was also upregulated by shear (11). While the mechanisms remain to be elucidated, an effect on TxA 2 synthase is consistent with an earlier observation that monkeys treated with testosterone exhibit elevated plasma levels of TxA 2 (45).…”
Section: Discussionsupporting
confidence: 79%
“…Alternatively, because testosterone exposure occurred in vivo, we cannot rule out indirect effects that could modulate the levels of TxA 2 synthase. For example, changes in shear stress were recently shown in human umbilical veins to affect TxA 2 expression; however, unlike testosterone exposure, prostacyclin synthase was also upregulated by shear (11). While the mechanisms remain to be elucidated, an effect on TxA 2 synthase is consistent with an earlier observation that monkeys treated with testosterone exhibit elevated plasma levels of TxA 2 (45).…”
Section: Discussionsupporting
confidence: 79%
“…2C and D). It has been reported that not only COX-2, but also COX-1 is induced in the vessel walls, either by the increased fluid shear stress or increased intraluminal pressure [11,12], although COX-1 is generally expressed constitutively. To examine the possibility whether shear stress or increased luminal pressure of the heart vessels was involved in the hypergravity-dependent COX-2 induction, we determined expression of COX-1 in the heart by immunohistochemistry.…”
Section: Resultsmentioning
confidence: 99%
“…3). Induction of both COX enzymes in the vessel walls strongly suggest that shear stress or increased inner pressure of -10-the vessels stimulates COX-2 expression [11,12]. It is possible that hemodynamic changes under hypergravity increased blood volume in the heart vessels, causing shear stress and increased pressure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29][30][31] Expression of COX-2 and biosynthesis of PGI 2 are upregulated by elevation of shear stress, a key regulator of vascular homeostasis. [32][33][34] COX-2 is a major source of PGI 2 in humans and a potent endogenous vasodilator and anti-atherogenic molecule. 32,35 PGI 2 prevents platelet aggregation, inhibits smooth muscle proliferation, and stimulates angiogenesis.…”
Section: Experimental Groupsmentioning
confidence: 99%